IMPLEMENTATION OF INTERNET OF THINGS (IOT) TO SIMULATE TEMPERATURE AND HUMIDITY IN NON STERILE MEDICINE PRODUCTION ROOMS USING TEMPERATURE SENSORS (LM 35) AND HUMIDITY SENSORS (DHT 22) BASED ON ARDUINO AND WEB - Mateus Bimahatma; Dani Sasmoko; Jarot Dian Susatyono (Journal of Technology Informatics and Engineering, 2023)
The development of increasingly sophisticated pharmaceutical industry technology requires researchers to develop technology in the pharmaceutical industry that can help employees carry out their duties. As we know, technology is very helpful in providing job data in industry. Information technology can improve the quality of work in industry. One of them is about monitoring temperature and humidity in the non-sterile drug production room. This temperature and humidity is monitored by the QA ( Quality Assurance )/Quality Assurance department, which is used to see whether the temperature and humidity of the non-sterile drug production room are well conditioned.Based on the existing problems, it is necessary to have an intelligent system that can monitor temperature and humidity precisely and periodically. One of them is creating an Internet of Things (IoT) Implementation tool for Simulating Temperature and Humidity in a Non-Sterile Medicine Production Room Using an Arduino and Web Based Temperature Sensor ( LM35 ) and Humidity Sensor ( DHT 22 ). This tool will periodically detect the temperature and humidity in each non-sterile drug production room. If the temperature exceeds the maximum limit in the non-sterile drug production room, the fan will turn on to release the hot air inside. All the data that has been collected will be processed by the Arduino Uno R3 Microcontroller and will be displayed on the website as an interface . For early detection, a DC Fan appears on the website that rotates if the temperature exceeds the maximum limit. Data transmission uses ESP8266 as a wireless module .